Phenomena Of Closing Sampradaya Ashram Krishna Balaram In Padang Galak By Traditional Kesiman Village In 2021 - Putra, Ida Bagus Rama Darma; Apriani, Kadek Dwita; Pramana, Gede Indra (Jurnal Nawala Politika, 2023)
This study explains the phenomenon of the closing of the Ashram Krishna Balaram sampradaya activities in the Kesiman Traditional Village. Sampradaya is an organization or association that carries out an understanding of teachings and ritual practices whose implementation procedures are not in accordance with the customs and traditions in Bali. Based on the phenomenon that occurred, there were data findings that the closure of sampradaya activities by the Kesiman Traditional Village in 2021 was based on an ethical violation committed by Ashram Krisna Balaram by spreading beliefs that were very different from the traditional dresta customs in Bali. The closure of the sampradaya activities was rejected by the Krishna Balaram Ashram Institute and the Bali Legal Aid Foundation (YLBH). Along with this, there are research results, namely the Traditional Village Council (MDA) together with Parisdha Hindu Dharma Indonesia (PHDI).